Declining Patriarchy and the Rise of Femininity; Discourse Analysis of the Leila’s Brothers Movie - Asal Razavi; Hossein Afrasiabi (زن در فرهنگ و هنر)
Discourses of power and their influence on social issues have recently garnered media attention and are represented in a variety of ways. The objective of this research is to analyze the discourse of patriarchy and its representation in Saeed Roustaei’s film “Leila's Brothers.” This investigation employs a qualitative methodology, specifically critical discourse analysis (CDA), as a result of its discourse approach and critical dimensions. CDA is implemented on four distinct levels: surface level, surface depth, depth level, and depth of depth. Dialogues, scenes, and language elements pertinent to the subject matter are chosen at the superficial level. These elements become more abstract and richer at a deeper level. Finally, the film’s concealed messages are analyzed by connecting linguistic elements to discourse practices at the depth of depth. The results indicate that the film contains two primary discourses: the decline of patriarchy (desperation, conservative reform, and the subsequent collapse of patriarchy) and the rise of femininity (female consciousness, imminent power of tyranny). The collapse of patriarchy is symbolized by "Leila's Brothers" in conjunction with the advancement of women. The film demonstrates that the cessation of patriarchy and the emergence of a women's discourse are currently being observed in contemporary society. The patriarchy is collapsing as women pursue a variety of professions. This film critiques and desacralizes the patriarchal position at the family and cultural levels, in contrast to the traditional sanctification of parents.